Measurable Levels of Short‐Chain Chlorinated Paraffins in Western Hudson Bay Fishes but Limited Biomagnification from Fish to Ringed Seals. (16th September 2021) - Facciola, Nadia; Pedro, Sara; Houde, Magali; Fisk, Aaron T.; Ferguson, Steven H.; Steer, Helena; Muir, Derek C. G.; McKinney, Melissa A.
Abstract: We investigated short‐chain (C10–13 ) chlorinated paraffins (SCCP) in an Arctic marine food web. In zooplankton, fishes, and ringed seals from western Hudson Bay, Canada, SCCP concentrations ranged from 38.3 to 687 ng g –1 lipid weight. Monte Carlo–simulated trophic‐adjusted biomagnification factors of individual SCCP congeners ranged from 0.07 to 0.55 for small pelagic fishes to seals. Despite relatively high concentrations in fishes, biomagnification of SCCPs within this food web appears limited. Environ Toxicol Chem 2021;40:2990–2999. © 2021 SETAC